(3eNJUQ JGQjN GdESdGes - (3GHf GdedG GdMUcaj , CMeO Hf eMeO Hf Ydj GdMUcaj GHf GdedG, GHf GdedG,J (B1003 (3g` s ((3GdeDda s)
(3ChdgG (B:s
(3GHf GdjSY hGfG YHO Gddg Hf CHj MaU s
(3BNQgG (B:s
(3GfJgJ GdWHbI GdSGHYI hGdKdGKhf ef JdNjU JGQjN GdESdGe Ydi jO edNUg hcGJHg GdTgjQ HGHf GdedGq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QGLY ajde Qbe (B180 (3chjJ h(B181 (3chjJs
(3YdjgG eWGdYI s
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
Keywords: (3GdJGQjNs